Effect of foam`s heterogeneity on the behaviour of sandwich panels - Chuda-Kowalska, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study aimed to develop a knowledge about material parameters identification of the foam core and numerical modelling of the sandwich panels to accurately predict the behaviour of this kind of structures. The polyisocyanurate foam (PIR) with low density used in sandwich panels dedicated to civil engineering is examined in the paper.
Keywords: sandwich panels; material parameters; PUR-PIR foam; heterogeneous core; DIC technique; płyty warstwowe; parametry materiałowe; pianka PUR-PIR; rdzeń heterogeniczny; technika DIC